Youth-Led Community-Based Tourism as a Catalyst for Destination Image Reconstruction: Evidence from Wane Beach, Indonesia - Feriyadin; Marwan; Abustam; Muzdalifah; Ade Rahayu Apriani (Faculty of Economics and Business, University of Mataram, 2026)
This study examines the transformation of Wane Beach in Bima Regency from a poorly-managed and insecure area into an emerging tourist destination. The purpose of this research is to analyze the revitalization process through a community-based tourism framework. The research employs a qualitative method with a case study design, focusing on the voluntary initiatives and collective actions spearheaded by local youth from Tolotangga and Tolouwi Villages. The results show that the transformation was achieved through a series of tangible, community-driven improvements. These included enhancing cleanliness, organizing parking areas and micro-enterprise stalls, providing basic facilities, constructing a prayer room, and strengthening security and visitor hospitality systems. The study concludes that the community-based tourism approach, fueled by the awareness and concern of local youth, has effectively reshaped both the image and reality of Wane Beach. This shift has turned a once-neglected location into a safe and comfortable destination, generating new economic prospects for the local community. The primary novelty of this research lies in documenting a grassroot, youth-led model for destination turnaround, demonstrating how community initiative can establish a foundational framework for sustainable tourism development without relying on top-down interventions.